Passivation of defects in Cs0.1FA0.9PbI3 perovskite films using zwitterionic molecules for enhanced performance - Maha AbuShawish; Hussain Alawadhi; Nouar Tabet (Materials Research Express, 2025)
Defect passivation in the bulk and at the surface of the perovskite absorbing layer is essential to enhance the efficiency and stability of perovskite solar cells. Many studies have investigated the effect of Lewis acids and bases on defect passivation, demonstrating their positive impact on device performance. However, the underlying passivation mechanisms remain a topic of debate. Recently, Machine Learning has been proposed to identify the key features of passivating agents, highlighting the need for more experimental data. In this study, we incorporate three zwitterionic molecules, Cysteine, Betaine, and Tyrosine, into the Cs _0.1 FA _0.9 PbI _3 perovskite layer and examine their impact on the photocarrier’s lifetime. Time-resolved photoluminescence (TRPL) measurements reveal a significant increase in photocarrier lifetime, indicating reduced non-radiative recombination. X-ray photoelectron spectroscopy (XPS) confirms zwitterion binding to the perovskite surface, reducing defect states. These findings highlight the potential of zwitterionic molecules as effective passivation agents for improving perovskite solar cells.